Travelers about folk healing of the Crimean Tatars (second half of the 19th century) - Liliya Gabdrafikova (Крымское историческое обозрение, 2019)
The object of this study is various guides and travel notes about the Crimea of the imperial period. These travelogues present a special picture of the daily life of the Crimean Tatars. In the 19th century, Crimean Tatars had interesting and original traditions of medical practices. This literature has stories about the life style of the Crimean Tatars, their attitude towards diseases and methods of healing. The authors of travel notes looked at the external image of the Crimean Tatars, at their public actions. For example, the pilgrimage of the Crimean Tatars to the “holy well”, dancing of Dervishes, etc. So, this system of medical practices of the Crimean Tatars (in the lens of the authors of travel notes) included pagan beliefs and rituals, Turkic food culture, healing methods associated with the Muslim culture. But they did not see the practice of folk healers of the Crimean Tatars. These works of the 19th century have the same assessments of folk practices of healing, where the authors contrasted “their” and “alien” culture. As a result this attitude hindered constructive dialogue between people of different cultures. But in the second half of the 19th century in the Crimea began intercultural interaction in the scope of public health. During this period the medical service of the zemstvo (municipality) was created, and the Crimean Tatars were in the zone of influence of this service. On the other hand, some methods of folk healing of the Crimean Tatars began to be used in the practice of official scientific medicine.